2017
DOI: 10.1139/cjz-2016-0233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental warming during early life history on libellulid odonates

Abstract: Climate warming affects ectotherms globally, yet we know little regarding the variability in species' responses to warming, particularly in early life stages. Additionally, intraspecific variation in response to warming is understudied but may determine species' resilience to warming. To assess how temperature affects egg development rate in co-occurring dragonfly species, we manipulated temperature (range: 22-31°C) and measured time to hatching. Warming decreased egg development time across all species, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…Increased temperature below the thermal optimum should increase growth and feeding rates in ectothermic organisms (Dell, Pawar, & Savage, ; Frances, Moon, & McCauley, ; Gresens, Cothran, & Thorp, ) and result in stronger priority effects (Grainger et al., ). Interestingly, our results did not support this prediction since the priority effects at the high temperature did not have stronger negative effects on life‐history traits than did the low temperature, that is we found no statistical interaction between treatment and temperature ( t test and Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased temperature below the thermal optimum should increase growth and feeding rates in ectothermic organisms (Dell, Pawar, & Savage, ; Frances, Moon, & McCauley, ; Gresens, Cothran, & Thorp, ) and result in stronger priority effects (Grainger et al., ). Interestingly, our results did not support this prediction since the priority effects at the high temperature did not have stronger negative effects on life‐history traits than did the low temperature, that is we found no statistical interaction between treatment and temperature ( t test and Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The year 2018 was drier but slightly cooler than 2019. The weather has an important influence on the life history of odonates (Hassall & Thompson, 2008;Frances et al, 2017;McCauley et al, 2018). Studies have shown experimentally that odonate larvae grow faster and emerge earlier under warmer conditions (Lutz, 1974;Pickup & Thompson, 1990), which explains the phenological shift that has been recorded during the past decades (Hassall et al, 2007;Dingemanse & Kalkman, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature is known to affect many aspects of the life history of Odonata (see review by Hassall and Thompson 2008). For example, increased temperature has been shown to affect egg development (Frances et al 2017), larval growth rates (Pritchard et al 2000, Suhling et al 2015, Frances et al 2017), larval survival (McCauley et al 2015, and sexual coloration (Moore et al 2018). As a consequence, the distribution of dragonflies and damselflies across the landscape may be determined by the thermal heterogeneity of the habitat and the sensitivity of the insect to temperature.…”
Section: Zygoptera -Coenagrionidaementioning
confidence: 99%